(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
One of the most common causes of liver cirrhosis is V and hepatitis C infection. World Health Organization According to information, liver cirrhosis is a chronic liver disease is the last stage, diffuse fibrosis and normal structure of the liver changes its place with the formation of nodes. This article provides information about the causes, course and prevention of cirrhosis of the liver.